Synthesis of racemic and chiral BEDT-TTF derivatives possessing hydroxy groups and their achiral and chiral charge transfer complexes - Krivickas, Sara Jane; Hashimoto, Chiho; Yoshida, Junya; Ueda, Akira; Takahashi, Kazuyuki; Wallis, John D.; Mori, Hatsumi (Beilstein Journal of Organic Chemistry, 2015)
Chiral molecular crystals built up by chiral molecules without inversion centers have attracted much interest owing to their versatile functionalities related to optical, magnetic, and electrical properties. However, there is a difficulty in chiral crystal growth due to the lack of symmetry. Therefore, we made the molecular design to introduce intermolecular hydrogen bonds in chiral crystals. Racemic and enantiopure bis(ethylenedithio)tetrathiafulvalene (BEDT-TTF) derivatives possessing hydroxymethyl groups as the source of hydrogen bonds were designed. The novel racemic trans-vic-(hydroxymethyl)(methyl)-BEDT-TTF 1, and racemic and enantiopure trans-vic-bis(hydroxymethyl)-BEDT-TTF 2 were synthesized. Moreover, the preparations, crystal structure analyses, and electrical resistivity measurements of the novel achiral charge transfer salt θ21-[(S,S)-2]3[(R,R)-2]3(ClO4)2 and the chiral salt α’-[(R,R)-2]ClO4(H2O) were carried out. In the former θ21-[(S,S)-2]3[(R,R)-2]3(ClO4)2, there are two sets of three crystallographically independent donor molecules [(S,S)-2]2[(R,R)-2] in a unit cell, where the two sets are related by an inversion center. The latter α’-[(R,R)-2]ClO4(H2O) is the chiral salt with included solvent H2O, which is not isostructural with the reported chiral salt α’-[(S,S)-2]ClO4 without H2O, but has a similar donor arrangement. According to the molecular design by introduction of hydroxy groups and a ClO4− anion, many intermediate-strength intermolecular hydrogen bonds (2.6–3.0 Å) were observed in these crystals between electron donor molecules, anions, and included H2O solvent, which improve the crystallinity and facilitate the extraction of physical properties. Both salts are semiconductors with relatively low resistivities at room temperature and activation energies of 1.2 ohm cm with Ea = 86 meV for θ21-[(S,S)-2]3[(R,R)-2]3(ClO4)2 and 0.6 ohm cm with Ea = 140 meV for α'-[(R,R)-2]2ClO4(H2O), respectively. The variety of donor arrangements, θ21 and two kinds of α’-types, and their electrical conductivities of charge transfer complexes based upon the racemic and enantiopure (S,S)-2, and (R,R)-2 donors originates not only from the chirality, but also the introduced intermolecular hydrogen bonds involving the hydroxymethyl groups, perchlorate anion, and the included solvent H2O.
Keywords: BEDT-TTF; chiral molecular crystal; hydrogen bonding; hydroxy group; molecular conductors